2019
DOI: 10.1016/j.neulet.2017.07.045
|View full text |Cite
|
Sign up to set email alerts
|

Historical pitfalls and new directions in the neuroscience of emotion

Abstract: In this article, we offer a brief history summarizing the last century of neuroscientific study of emotion, highlighting dominant themes that run through various schools of thought. We then summarize the current state of the field, followed by six key points for scientific progress that are inspired by a multi-level constructivist theory of emotion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(107 citation statements)
references
References 138 publications
2
91
0
2
Order By: Relevance
“…While external experience refers to sights, sounds, and smells, internal experience refers to sensations, cognitions, and emotions. According to the James‐Lange theory and somatic marker hypothesis (Damasio & Carvalho, ), emotions have been understood more recently by neuroscientists (Barrett & Satpute, ) as being based on the central processing of interoceptive sensations and feelings. This is captured by the MAIA subscale for Emotional Awareness, the tendency to be aware of the connection between body sensations and emotional states.…”
Section: Discussionmentioning
confidence: 99%
“…While external experience refers to sights, sounds, and smells, internal experience refers to sensations, cognitions, and emotions. According to the James‐Lange theory and somatic marker hypothesis (Damasio & Carvalho, ), emotions have been understood more recently by neuroscientists (Barrett & Satpute, ) as being based on the central processing of interoceptive sensations and feelings. This is captured by the MAIA subscale for Emotional Awareness, the tendency to be aware of the connection between body sensations and emotional states.…”
Section: Discussionmentioning
confidence: 99%
“…In our opinions, this would mean at least six things. First, self-injurious thoughts and behaviors work like most other psychological phenomena, which are complex on the level of biopsychosocial factors [e.g., emotions: see (23,24)]. Second, the causes, predictors, and correlates of self-injurious thoughts and behaviors are indeterminate (i.e., show degeneracy and pluripotentiality, which are core feature of complex systems), but they are not random.…”
Section: Discussionmentioning
confidence: 99%
“…To demonstrate that one factor or one factor combination is necessary, it must be shown that no other algorithms with different factors or factor combinations are also sufficient (i.e., yields good classification accuracy). simple (16,20,(22)(23)(24)(25)(26). We likewise hypothesize that the differences between people who engage in NSSI and people who attempt suicide are complex rather than complicated or simple.…”
Section: Nssi and Suicide Attempt Examplesmentioning
confidence: 93%
“…Cerebral vascular regulation is also thought to be based on predictive coding: the hemodynamic response anticipates neural firing in order to prevent a mismatch in blood supply and demand (Das & Sirotin, ; Philips, Chhabria, & Chakravarthy, ; Sirotin & Das, ). Thus, common mechanisms may support emotional perception, interoception, and bodily and cerebrovascular regulation (Barrett & Satpute, ).…”
Section: Introductionmentioning
confidence: 99%